The impact of the BrainBoosters programme on foundational mathematics learning in early childhood education for English second language learners - Naude, Mariana; Meier, Corinne (African Perspectives of Research in Teaching and Learning Journal, 2024)
The poor mathematics performance of South African learners is alarming. A solution is to lay a solid foundation for mathematics learning in early childhood education, using learners’ home language as language of learning and teaching. However, most early childhood learners are English Second Language speakers who are instructed in English. This study aimed at establishing the value of the BrainBoosters mathematics programme, for English Second Language learners in Early Childhood Education. A qualitative case study informed by the interpretivist paradigm gathered data from two preschools which use English as language of learning and teaching in Pretoria, South Africa. Purposeful sampling was used to select two teachers who implemented the BrainBoosters programme in two classes of 15 English Second Language learners, aged 3-5 years, over six weeks. Data were gathered by classroom observations, interviews with teachers and interviews with three Early Childhood Education experts. Data were analysed using thematic content analysis. The results indicated the value of the BrainBoosters programme for early mathematics learning in the English Second Language context and its provision of a positive language learning environment. Direct instruction was effective for learning mathematical concepts; however, activities were insufficiently contextualised. Excessive reinforcement caused learner disengagement. The usefulness of the BrainBoosters programme should be enhanced by a more flexible constructivist approach to the learning of mathematics in Early Childhood Education in English Second Language context.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 4, Volume 8, 2024
Keywords: BrainBoosters; Direct instruction; Early childhood education; English Second Language learners; Mathematics; Case study.; Mathematic ability -- testing; Mathematics; Mathematics -- Study and teaching; Early childhood education -- South Africa; English language -- Study and teaching -- Foreign speakers